Novel antitumor therapeutic strategy using CD4+ T cell-derived extracellular vesicles. (October 2022) - Shin, Sanghee; Jung, Inseong; Jung, Dokyung; Kim, Christine Seulki; Kang, Sung-Min; Ryu, Suyeon; Choi, Sung-Jin; Noh, Soojeong; Jeong, Jongwon; Lee, Beom Yong; Park, Jun-Kook; Shin, Jiwon; et al.
Abstract: Extracellular vesicles (EVs) mediate cell-cell crosstalk by carrying bioactive molecules derived from cells. Recently, immune cell-derived EVs have been reported to regulate key biological functions such as tumor progression. CD4 + T cells orchestrate overall immunity; however, the biological role of their EVs is unclear. This study reveals that EVs derived from CD4 + T cells increase the antitumor response of CD8 + T cells by enhancing their proliferation and activity without affecting regulatory T cells (Tregs). Moreover, EVs derived from interleukin-2 (IL2)-stimulated CD4 + T cells induce a more enhanced antitumor response of CD8 + T cells compared with that of IL2-unstimulated CD4 + T cell-derived EVs. Mechanistically, miR-25-3p, miR-155-5p, miR-215-5p, and miR-375 within CD4 + T cell-derived EVs are responsible for the induction of CD8 + T cell-mediated antitumor responses. In a melanoma mouse model, the EVs potently suppress tumor growth through CD8 + T cell activation. This study demonstrates that the EVs, in addition to IL2, are important mediators between CD4 + and CD8 + T cells. Furthermore, unlike IL2, clinically used as an antitumor agent, CD4 + T cell-derived EVs stimulate CD8 + T cells without activating Tregs. Therefore, CD4 + T cell-derived EVs may provide a novel direction for cancer immunotherapy by inducing a CD8 + T cell-mediated antitumor response.